Sistem Kendali dan Akuisisi Data Suhu Serta Kelembaban Ruang Budidaya Jamur Tiram (Pleurotus Ostreatus) Berbasis Internet Of Things (IOT) - Rohmah, Amalia; Dewanto, Satriyo Agung (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2019)
This study aims to determine the performance of temperature and humidity control technology of the Internet of Things (IoT) automatic oyster mushroom cultivation space. The stages of device development consist of analysis, design, assembly and testing. The design developed combines hardware control, software, and cloud server. This tool consists of 3 main processes, namely input using DHT11 sensors, process and output, namely 220 V AC actuators. There are two tests namely technical and effectiveness. The test results that have been carried out are: (1) the performance test results obtained an average error of 1.44% and a mean humidity of 3.35%, so that it can be used properly in the process of oyster mushroom cultivation; (2) the actuator will turn on if the temperature is more than 28oC or the humidity is less than 70%. The results of the transmission and storage of hardware data to the software on the database function properly, testing the effectiveness which shows the tools developed are more effective 5 hours compared to the manual method, (3) The advantages of this tool are that it can work automatically with IoT technology, there is realtime data recording, and features that are easy to use, so that it can help farmers in the care of oyster mushrooms.